Association between COVID-19 anxiety syndrome and COVID-19 vaccine hesitancy in the postpandemic era: a cross-sectional study in Hong Kong - Timothy Chung Ming Wu; Jonathan Ka Ming Ho; Sai Kit Choi; Yanki Hiu Yan Chan; Bella Wing Sze Chan; Timmy Tim Ming Li; Fu Po Tam; Ivan Man Chun Wong; Alex Siu Wing Chan (BMC Public Health)
Abstract Background The COVID-19 pandemic has had profound psychophysiological and socioeconomic effects worldwide. COVID-19 anxiety syndrome (CAS) is a specific cluster of maladaptive coping strategies, including perseveration and avoidance behaviours, in response to the perceived threat and fear of COVID-19. CAS is distinct from general COVID-19 anxiety. The level of CAS in the postpandemic era remained unknown. Despite extensive research on general COVID-19 anxiety and COVID-19 vaccine hesitancy (CVH), few studies have investigated the association between CAS and CVH. The present study aimed to assess the level of CAS and the prevalence of CVH and explore the association between CAS and CVH in the general population of Hong Kong. Methods This cross-sectional study was conducted in Hong Kong. Participants were recruited using convenience and snowball sampling methods and completed an online or a paper-based questionnaire comprising two well-validated instruments. The COVID-19 Anxiety Syndrome Scale (C-19ASS), which includes the C-19ASS-P and C-19ASS-A subscales, was used to evaluate CAS in terms of perseveration and avoidance behaviours. The COVID-19 Vaccine Hesitancy Scale (CVHS) was used to determine the presence of CVH. Results This study included 389 participants. The median C-19ASS-P and C-19ASS-A scores were 8 (Interquartile range (IQR) 5–13) and 3 (IQR 0–6), respectively. The CVHS scores revealed a CVH prevalence of 68.1%. A significantly larger proportion of participants with CVH rated “hesitant” compared with those without CVH across all the CVHS items. Furthermore, the median C-19ASS-P and C-19ASS-A scores were significantly higher for participants without CVH than for those with CVH. Conclusions Our findings revealed that CAS persists and CVH is common in the postpandemic era and that CAS is associated with CVH. Comprehensive interventions addressing both informational and psychological aspects are needed to increase the rate of vaccine acceptance and to mitigate the effect of CAS on public health outcomes.